Narrating the First "Three-Parent Baby": The Initial Press Reactions From the United Kingdom, the United States, and Mexico. Issue 4 (August 2018) - González Santos, Sandra P.; Stephens, Neil; Dimond, Rebecca
In 2016, the New Scientist announced the birth and good health of the world's first baby conceived using spindle nuclear transfer (SNT). The story was immediately circulated worldwide. In this article, we analyze 39 articles published within the first 48 hours of the announcement, in the Mexican, British, and U.S. press. These articles constitute the initial press reactions to the announcement, and as such, they offer a narrative ground on which SNT could thereafter be discussed. We argue that as a media event, the articles performed the task of rendering SNT, a "cultural novelty, " as culturally and technologically feasible.